Endophytic fungi of Euterpe edulis (açaí-do-sul) fruits: antimicrobial activity and its relation with the growing medium - Garbin, Vivien Patrícia; Helm, Cristiane Vieira; Dalzoto, Patrícia do Rocio; Stuart, Andressa Katiski da Costa; Romagnoli, Bruno Accioly Alves; Pires, Thiago de Farias; Pimentel, Ida Chapaval (Revista de Ciências Agro-Ambientais, 2020)
Euterpe edulis (açaí-do-sul) have wide nutritional, pharmaceutical and industrial applications. Its extensive exploitation threatens this species with extinction. The endophytic fungi can produce similar compounds to their hosts. Thus, the present study is aimed to isolate endophytic fungi from the fruits of E. edulis and to evaluate their antimicrobial activities against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, MRSA, and Candida albicans and the interference of the culture medium. Fungi were isolated in potato dextrose agar (PDA) medium. The isolates were characterized by morphology. The main genera isolated were Fusarium, Alternaria, Penicillium, Trichoderma, Acremonium and Aspergillus. The isolate Penicillium EFP1 shows antimicrobial activity against all the pathogens tested in PDA plus extract (PDAA). When in Sabouraud plus extract (SDAA), Penicillium EFP1 was able to inhibit all pathogens, except for P. aeroginosa. Trichoderma EFT. On the other hand, it only inhibited E. coli, S. aureus and MRSA, and the addition of the extract decreased the inhibition efficiency. The isolate Penicillium EFP1 presented significant inhibitory activity against pathogens, evidencing the potential for research papers in view of industrial interest and metabolites exploitation.